Competing models of linguistic change : evolution and beyond - Nedergaard Thomsen, Ole (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 2006)
The articles of this volume are centered around two competing views on language change originally presented at the 2003 International Conference on Historical Linguistics in the two important plenary papers by Henning Andersen and William Croft. The latter proposes an evolutionary model of language change within a domain-neutral model of a 'generalized analysis of selection', whereas Henning Andersen takes it that cultural phenomena could not possibly be handled, i.e. observed, described, understood, in the same way as natural phenomena. These papers are models of succinct presentation of impo.